Research-Based Writing Practices and the Common Core: Meta-Analysis and Meta-Synthesis - Graham, Steve; Harris, Karen R; Santangelo, Tanya (The Elementary school journal, 2015)
In order to meet writing objectives specified in the Common Core State Standards (CCSS), many teachers need to make significant changes in how writing is taught. While CCSS identified what students need to master, it did not provide guidance on how teachers are to meet these writing benchmarks. The current article presents research-supported practices that can be used to meet CCSS writing objectives in kindergarten to grade 8. We identified these practices by conducting a new meta-analysis of writing intervention studies, which included true and quasi-experiments, as well as single-subject design studies. In addition, we conducted a meta-synthesis of qualitative studies examining the practices of exceptional literacy teachers. Studies in 20 previous reviews served as the data source for these analyses. The recommended practices derived from these analyses are presented within a framework that takes into account both the social contextual and cognitive/motivational nature of writing.